Strategic planning in universities: a case of Ukraine - Tetiana Ponomarenko (Problems and Perspectives in Management, 2018)
The effective management core principles include the obligatory approval of the orga¬nization’s mission and its strategic plan availability. This also applies to specific organizations such as universities. The purpose of the article is to test the hypothesis that to date, most Ukrainian universities do not care about the presence of such attributes of effective performance (at least, they do not publish them on their sites). The site analysis was carried out in the top 50 out of 289 universities in Ukraine. It turned out that 29 out of these 50 have no mission (do not publish it on the site), and eight universities do not have a strategy. It is established that the most common mistakes in the strategy development are the lack of quantitative indicators, giving a special attention to the coverage of the results achieved; inclusion in the text of the document the thematic sections, which do not concern the prospects of university development, etc.